New mechanical labour induction kits - Nusee, Zalina; Romli, Afifuddin; Romli, Ahmad Zafir; Nik Ibrahim, Nik Noor Idayu; Ismail, Hamizah (2019)
The present invention relates to preparation for induced labour in a pregnant woman, and more particularly to a device for promoting cervical ripening and dilation during the induction of labour.